Technical and non-technical losses calculation in distribution grids using a defined equivalent operational impedance - Manito, Allan R.A; Bezerra, Ubiratan H; Soares, Thiago M; Vieira, João P.A; Nunes, Marcus V.A; Tostes, Maria E.L; de Oliveira, Rafael C (IET generation, transmission & distribution, 2019)
This study presents an approach to calculate average technical losses (TLoss) and non-technical losses (NTLoss) in distribution grids using an equivalent operational impedance (EOI) calculated from a load flow solution for the transformers’ average loads, obtained from customers’ electric bills. If transformers are supervised, i.e. have available active and reactive power injections measurements or estimates from a state estimator program, the transformers’ average technical and non-technical losses can be calculated by running a load flow for the grid supplied by the transformer and using the definition of EOI presented in this study. For unsupervised transformers, i.e. no measurements or estimates are available, pseudo measurements of average active and reactive power injections can be obtained by a procedure that uses active and reactive power measurements at the feeder substation. The use of this methodology by electric utilities allows the calculation of technical and non-technical losses more accurately, as well as the inclusion of non-technical losses in the distribution networks operation planning. Results using the IEEE 13-bus test system and an urban real distribution grid are presented to demonstrate the effectiveness of the proposed methodology.